HIV infection risk perception and stigmatizing attitude: Results of surveys of dwellers from the Central Administrative District of Moscow - V V Belyaeva; M M Adigamov; E V Sokolova; M О Orlova (Терапевтический архив, 2015)
Aim. To study human immunodeficiency virus (HIV) infection risk perception and stigmatizing attitudes in the dwellers of the Central Administrative District of Moscow. Subjects and methods. An anonymous survey was conducted using specially developed questionnaires. A total of 893 people were interviewed. Each of the given indicators was used to ask 98 to 254 respondents. Among the survey participants, there were 92 healthcare workers, including 66 physicians and 26 representatives of middle-level and junior medical staff. According to their replies, the respondents were divided into 2 groups: 1) healthcare workers; 2) representatives of the so-called general population. Results. 91.3% of the healthcare workers gave a negative reply to the question: «Should contacts (intercourse) with people living with HIV (AIDS) be avoided to escape infection?». In Group 2, 58.8 and 23.5% of the respondents answered negatively and positively, respectively; and 17.6% had difficulty answering the question. In the general population group, 44.1% of the respondents answered negatively and 32.2% had difficulty answering the question: «Would you agree to live in the same room with anybody whom you know or suspect to be HIV positive?»; 23.8% agreed to do this. Among the healthcare workers, there were 46.7% of the respondents who answered positively. When the question: «Would you agree to send your child (grandson) to the kindergarten if you would learn that a HIV-infected child goes there?» was asked, 48.6 and 18.7% of the respondents in the general population group answered negatively and positively, respectively; 32.7% had difficulty answering. In the group of healthcare workers, 66.7% answered positively. Among both the healthcare workers and the representatives of the general population, more than 60% of the respondents agreed with the statement that «HIV-infected people lead a loose life». Conclusion. The specific features of perceiving a HIV infection risk and showing stigmatizing attitudes towards HIV-infected patients make the forming less dangerous behaviors difficult and restrict an access to care and support in infected patients. The training of healthcare workers in issues related to HIV infection should involve the identification of stigmatizing attitudes and the application of destigmatization strategies.